2015
DOI: 10.17306/j.npt.2015.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Maiden pear trees growth in replant soil after inoculation of rootstocks with mycorrhizal inoculum

Abstract: Summary. In the production of fruit trees it is important to set up a nursery always in a new site, alternatively to follow crop rotation rules. It is not always possible due to the size of a farm and production volume. In order to limit the effects of replant soil one can use different procedures before setting up a nursery. Chemical methods, however, must be replaced with non chemical ones due to environmental protection and reduction of production costs. In the experiment conducted in 2009-2012, growth of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…was similar to that of the trees in the CRS treatment. Our experiment confirmed the findings of earlier studies which showed that mycorrhization had positive effect on the growth of roots of some species of fruit trees, i.e., apple trees [47], pear trees [48], sour cherry trees [49], and plum trees [50]. The results of studies conducted by other researchers showed that mycorrhizal fungi improved the vegetative growth of apple trees [51], sour cherry trees [52], cherry rootstocks [53], and strawberries [54].…”
Section: The Influence Of Soil Preparations On the Growth Power Of Ap...supporting
confidence: 91%
“…was similar to that of the trees in the CRS treatment. Our experiment confirmed the findings of earlier studies which showed that mycorrhization had positive effect on the growth of roots of some species of fruit trees, i.e., apple trees [47], pear trees [48], sour cherry trees [49], and plum trees [50]. The results of studies conducted by other researchers showed that mycorrhizal fungi improved the vegetative growth of apple trees [51], sour cherry trees [52], cherry rootstocks [53], and strawberries [54].…”
Section: The Influence Of Soil Preparations On the Growth Power Of Ap...supporting
confidence: 91%